PENGARUH KUALITAS PRODUK, CITRA MEREK, PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK PIXY DI KOTA BOGOR - Syaiful Anwar; Arini Putriani; Muchammad Hamdani; Ridwan; Erna Herlina (Economicus, 2024)
The purpose of this study is to determine the influence of Product Quality, Brand Image, Promotion and Price on Purchase Decisions of PIXY Cosmetic Products in Bogor City. The research method used is Quantitative Causality research. The type of data studied is Quantitative data, which is primary data. Based on the results of the partial significance test (t-test), it was obtained that the values of the Product Quality and promotion variables had a significant partial effect on the purchase decision of PIXY cosmetic products in Bogor City, while the Brand Image and price variables had no effect. Furthermore, the results of the simultaneous significance test (F-test) obtained results together the variables of Product Quality, Brand Image, Promotion and Price have an influence on the purchase decision. The results of the determination coefficient test are known that the value of the determination coefficient (adjusted R Square) obtained is 0.496, which means that 49.6% of purchase decisions are influenced by Product Quality, Brand Image, Promotion, and Price, while the remaining 50.4% of purchase decisions are influenced by other variables that are not studied in this study.